Load distribution mesh routing for wireless mesh network - Ibrahim, Ismadi (2015)
Wireless Mesh Network (WMN) has been strongly investigated by many researchers because of its potential to extend network connectivity to various network scenarios such as in internet broadband access and Wireless Local Area Network (WLAN). WMN comprises of multiple wireless routers that relay packets in a multihop fashion such as in ad hoc network. These mesh routers are connected to mesh clients, which can be any other type of ad hoc networks and they can also communicate with the Internet through one or more gateways. Routing protocol is very important in WMN because it is responsible to forward packet from the source to the destination. The primary objective of this research is to develop a routing protocol namely Load Distributed Mesh Routing (LDMR) protocol that is specifically designed for WMN with IEEE 802.11 standard. The proposed LDMR protocol is developed according to the design concept of Real Time Load Distribution (RTLD) routing protocol that is designed for Wireless Sensor Network (WSN).The LDMR protocol determines potential next hop node based on quadrant and distance information. Then, the Next Hop Forwarding (NHF) decision is used to select the best next hop nodes based on Packet Success Rate (PSR) and maximum velocity of a packet.In addition, a new module of the proposed LDMR protocol is developed in Network Simulator 3 (ns3). The proposed LDMR protocol has been successfully studied and verified through simulation. The WMN’s performance is measured in terms of throughput and average end-to-end delay for both randomly distributed and grid network topologies. The network performance of LDMR is compared with the existing routing protocol, which are Ad Hoc on Demand Distance Vector (AODV) and Hybrid Wireless Mesh Protocol (HWMP). Simulation results show that LDMR protocol outperforms other protocols in most of the simulated scenarios where the highest improvement of throughput is 67.39% than HWMP and 60.15% than AODV in the scenario where the connections from multiple sources are routed to a single destination. The LDMR protocol also maintains a low average endto- end delay which is lower than 0.01s in almost all cases when compared with AODV and HWMP protocols. The proposed LDMR routing protocol in this research has significantly enhanced the network performance in WMN.